Positive electrode active material for lithium ion secondary battery, method for producing positive electrode active material for lithium ion secondary battery, and lithium ion secondary battery
By using lithium transition metal composite oxide with a layered rock salt structure and a positive electrode active material of crystalline lithium phosphate in lithium ion secondary batteries, the element ratio is controlled and secondary particles is formed, the problem of the reduction of the capacity of the positive electrode active material during the circulation process is solved, and the circulation performance and battery capacity of the battery are improved.
Patent Information
- Application Number
- JP2023123254
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-28
- Publication Date
- 2025-02-07
AI Technical Summary
The existing positive electrode active materials have poor circulation performance in lithium-ion secondary batteries, especially in the repeated charging and discharging process, and the capacity is significantly reduced.
The positive electrode active material containing lithium transition metal composite oxides with a layered rock salt structure and crystalline lithium phosphate is used to control the proportion of elements outside the lithium site between 3% and 8%, and secondary particles are formed through mechanical ball milling and heat treatment to ensure the uniform distribution of elements.
The circulation characteristics and battery capacity of lithium-ion secondary batteries are improved, the irreversible movement of elements during charging and discharging is reduced, and the stability of the crystal structure is enhanced.
Smart Images

Figure 2025019577000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a positive electrode active material for a lithium ion secondary battery, a method for producing a positive electrode active material for a lithium ion secondary battery, and a lithium ion secondary battery. [Background technology]
[0002] In recent years, there has been a strong demand for secondary batteries with high energy density to extend the driving range of electric vehicles (hereinafter also referred to as "EVs"). As such secondary batteries, lithium-ion secondary batteries that use lithium, lithium alloys, metal oxides, or carbon as the negative electrode have attracted attention.
[0003] With the aim of further improving the performance of lithium ion secondary batteries, positive electrode active materials for use in lithium ion secondary batteries have been studied and proposed.
[0004] The positive electrode active material used in the positive electrode of lithium-ion secondary batteries for EVs is, for example, LiNi 1-x-y Co x Al y NCA is a positive electrode active material in which part of the Ni in lithium nickel oxide: LiNiO2 (hereinafter also referred to as "LNO") is replaced with Co and Al, and the Co substitution suppresses changes in the crystal structure during charging and discharging, while the Al substitution improves thermal stability.
[0005] For example, Patent Document 1 discloses a positive electrode mixture for a non-aqueous electrolyte secondary battery that contains a particulate positive electrode active material made of a transition metal composite oxide, and lists lithium cobalt oxide (LiCoO2) and the like as the transition metal composite oxide.
[0006] Patent Document 2 discloses positive electrode active material particles containing a lithium salt of a transition oxide having a layered rock salt structure. x Co y M zO2 (where M is Al or Mn, 0 < x < 1, 0 < y < 1, x + y + z = 1) is disclosed.
Prior Art Documents
Patent Documents
[0007]
Patent Document 1
Patent Document 2
Summary of the Invention
Problems to be Solved by the Invention
[0008] However, the cathode active materials disclosed in Patent Documents 1 and 2 have a problem that when applied to a lithium-ion secondary battery and repeatedly charged and discharged, the capacity decrease is large.
[0009] Therefore, in view of the problems of the above prior art, one aspect of the present invention aims to provide a cathode active material for a lithium-ion secondary battery having excellent cycle characteristics when used in a lithium-ion secondary battery.
Means for Solving the Problems
[0010] According to one embodiment of the present invention for solving the above problems, a cathode active material for a lithium-ion secondary battery including secondary particles in which a plurality of primary particles are aggregated with each other, including a lithium transition metal composite oxide having a layered rock salt structure and crystallized lithium phosphate, in the crystal structure analysis by neutron diffraction of the lithium transition metal composite oxide having the layered rock salt structure, a cathode active material for a lithium-ion secondary battery is provided, in which the ratio of elements other than lithium occupying the lithium site (3b site) is 3% or more and 8% or less.
Effects of the Invention
[0011] According to one embodiment of the present invention, it is possible to provide a positive electrode active material for a lithium ion secondary battery that has excellent cycle characteristics when used in a lithium ion secondary battery. [Brief description of the drawings]
[0012] [Figure 1] FIG. 1 shows a flow of a method for producing a positive electrode active material for a lithium ion secondary battery. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] Hereinafter, the form for carrying out the present invention will be described with reference to the drawings. However, the present invention is not limited to the following embodiment, and various modifications and substitutions can be made to the following embodiment without departing from the scope of the present invention. [Positive electrode active material for lithium-ion secondary batteries] Hereinafter, the positive electrode active material for a lithium ion secondary battery of this embodiment (hereinafter also simply referred to as "positive electrode active material", and the lithium ion secondary battery is also simply referred to as "secondary battery") will be described. (1) Positive electrode active material The positive electrode active material of this embodiment contains a lithium transition metal composite oxide having a layered rock salt structure and crystallized lithium phosphate. The positive electrode active material of this embodiment may be composed only of a lithium transition metal composite oxide and crystallized lithium phosphate, but even in this case, it does not exclude the inclusion of unavoidable impurities that are mixed in during the manufacturing process, etc. (1-1) Particle morphology The particle shape of the positive electrode active material of this embodiment is not particularly limited, but the positive electrode active material of this embodiment may contain secondary particles in which a plurality of primary particles are aggregated together. Therefore, the positive electrode active material of this embodiment may be composed only of secondary particles, or may contain primary particles that exist independently without aggregation in addition to the secondary particles.
[0014] The particles of the positive electrode active material of this embodiment can include particles of a lithium transition metal composite oxide, and the primary particles and secondary particles contained in the positive electrode active material of this embodiment may be primary particles and secondary particles of a lithium transition metal composite oxide.
[0015] The particle morphology of the positive electrode active material of this embodiment can be roughly confirmed by a scanning electron microscope (SEM) observation image (hereinafter also referred to as "SEM image") of the particle appearance, but it may lack accuracy. In the positive electrode active material of this embodiment, it is preferable to process the cross section of the particle and use the SEM image to determine the presence or absence of primary particles and secondary particles.
[0016] Specifically, for example, it is preferable to embed particles of the positive electrode active material in a resin, and then perform cross-section polishing (CP) processing or the like to make the cross-section of the particles observable, and then observe the SEM image to determine the presence or absence of primary particles and secondary particles. For the determination, it is preferable to perform the above evaluation on 50 or more particles. There is no particular upper limit on the number of particles to be evaluated, but it is preferable to perform the evaluation on 200 or less particles in consideration of the productivity of the evaluation.
[0017] In addition, the above particle cross-sections can be confirmed using band contrast in the electron backscatter diffraction (hereinafter also referred to as "EBSD") method, or when using a focused ion beam (FIB) processing device for cross-section processing, using the attached scanning ion microscope (SIM) observation image.
[0018] The crystallized lithium phosphate contained in the positive electrode active material of this embodiment preferably covers at least a part of the surface of the primary particles of the lithium transition metal composite oxide having a layered rock salt structure, and further preferably is dispersed inside or on the surface of the secondary particles of the lithium transition metal composite oxide having a layered rock salt structure.
[0019] The crystallized lithium phosphate covers at least a part of the surface of the primary particles of the lithium transition metal composite oxide and is dispersed inside or on the surface of the secondary particles of the lithium transition metal composite oxide, thereby improving the cycle characteristics when the positive electrode active material of this embodiment is applied to a secondary battery. Although the reason for this is not clear, it is thought that by disposing lithium phosphate on the surface of the primary particles of the lithium transition metal composite oxide or inside or on the surface of the secondary particles, the reaction between the electrolyte and the lithium transition metal composite oxide can be suppressed, and the lithium phosphate alleviates the expansion and contraction of the lithium transition metal composite oxide that accompanies charging and discharging. (1-2) Proportion of elements other than lithium in the lithium site (3b site) In a crystal structure analysis by neutron diffraction of the lithium transition metal composite oxide having a layered rock-salt structure contained in the positive electrode active material according to this embodiment, the ratio of elements other than lithium in the lithium sites (3b sites) is preferably 3% or more and 8% or less, and more preferably 4% or more and 7% or less.
[0020] The ratio of elements other than lithium to the lithium site (3b site) means the ratio of elements other than lithium and oxygen, for example, metal elements other than lithium, to the lithium site (3b site). The ratio of elements other than lithium to the lithium site (3b site) can be obtained by analyzing a neutron diffraction pattern measured by a neutron diffraction method using the Rietveld method. When analyzing using the Rietveld method, a layered rock salt structure, which is a crystal structure of a lithium transition metal composite oxide, can be used as the crystal structure.
[0021] When a secondary battery is repeatedly charged and discharged, lithium is repeatedly inserted and removed between the layers of the lithium transition metal composite oxide. However, when a secondary battery using a conventional positive electrode active material is repeatedly charged and discharged, elements other than lithium that were located at the metal site (3b site) may irreversibly migrate to the tetrahedral site (6c site).
[0022] In contrast, in the lithium transition metal composite oxide contained in the positive electrode active material of this embodiment, the ratio of elements other than lithium to the lithium sites (3b sites) is 3% or more. It is believed that by inserting elements other than lithium into the lithium sites in advance in this way, it is possible to suppress the irreversible movement of elements other than lithium to the tetrahedral sites (6c sites) during charging and discharging. Therefore, it is believed that the change in the crystal structure of the lithium transition metal composite oxide is suppressed when charging and discharging are repeated, and the cycle characteristics can be improved.
[0023] In addition, by limiting the proportion of elements other than lithium in the lithium sites (3b sites) to 8% or less, the deterioration of the perfection of the crystals of the lithium transition metal composite oxide can be suppressed, which ensures a sufficient amount of lithium that contributes to charging and discharging, suppresses reaction resistance, and sufficiently increases battery capacity and output. (1-3) Ratio of lithium elements in metal sites (3a sites) In a crystal structure analysis by neutron diffraction of a lithium transition metal composite oxide having a layered rock-salt structure, the proportion of lithium elements in the metal sites (3a sites) is preferably 3% or more and 8% or less.
[0024] The lithium element inserted into the metal site (3a site) is derived from the lithium element inserted into the lithium site (3b site) that has been replaced by an element other than lithium. In other words, the lithium element inserted into the metal site (3a site) is the lithium element that should have been inserted into the lithium site (3b site).
[0025] By setting the ratio of lithium elements in the metal sites (3a sites) to 3% or more and 8% or less, the substituted lithium remains within the crystal structure, which prevents the deterioration of the crystal integrity of the lithium transition metal composite oxide. This suppresses reaction resistance and sufficiently increases the battery capacity and output. (1-4) Composition of positive electrode active material The composition of the positive electrode active material of this embodiment is not particularly limited, but is preferably a compound having the general formula: kLiPO4-(1-k)Li sNi 1-x-y-z Co x Mn y M z O 2+α It is preferably represented by
[0026] In the above general formula, k, x, y, z, s, and α preferably satisfy the relationships of 0 < k < 0.1, 0 ≤ x ≤ 0.35, 0 ≤ y ≤ 0.35, 0 ≤ z ≤ 0.10, 1.00 ≤ s < 1.30, and 0 ≤ α ≤ 0.2. Further, the element M in the above general formula can be at least one element selected from V, Mg, Mo, Nb, Ti, W, and Al.
[0027] In the above general formula, Li3PO4 corresponds to lithium phosphate, and Li s Ni 1-x-y-z Co x Mn y M z O 2+α corresponds to the lithium transition metal composite oxide. As is clear from the above general formula, lithium phosphate is preferably contained in a proportion of more than 0 mol% and less than 10 mol% in terms of the amount of substance out of the total of the lithium phosphate and the lithium transition metal composite oxide contained in the positive electrode active material.
[0028] Further, lithium phosphate (Li3PO4) is preferably 10 wt% or less, more preferably 5 wt% or less, based on the lithium transition metal composite oxide (Li s Ni 1-x-y-z Co x Mn y M z O 2+α ).
[0029] Note that the composition of the lithium transition metal composite oxide can be measured by quantitative analysis using inductively coupled plasma (ICP) optical emission spectrometry. (1-5) Average particle diameter of primary particles The positive electrode active material of the present embodiment preferably has an average particle diameter of the primary particles of 20 nm or more and 250 nm or less, more preferably 20 nm or more and 150 nm or less, and even more preferably 70 nm or more and 150 nm or less.
[0030] By making the average particle diameter of the primary particles of the positive electrode active material of this embodiment 20 nm or more, it means that the size of the primary particles contained in the positive electrode active material of this embodiment and the crystallites constituting the primary particles can be made sufficiently large. Therefore, the crystallinity of the lithium transition metal composite oxide contained in the positive electrode active material can be increased, and when the positive electrode active material of this embodiment is applied to a secondary battery, the battery capacity can be increased, and a secondary battery excellent in battery capacity and cycle characteristics can be obtained.
[0031] As described above, the lithium transition metal composite oxide contained in the positive electrode active material of this embodiment has an element other than Li inserted into the Li site (3b site). In this way, the insertion of an element other than Li into the Li site may reduce the diffusibility of Li during charging and discharging. In response to this, the average particle size of the primary particles of the positive electrode active material of this embodiment is set to 250 nm or less, so that the diffusion distance of Li can be reduced. Therefore, the decrease in diffusibility of Li caused by the insertion of an element other than Li into the Li site (3b site) is suppressed, and the capacity and output characteristics can be improved when applied to a secondary battery.
[0032] The average particle size of the primary particles of the positive electrode active material is determined by selecting primary particles of the positive electrode active material that can be observed in their entirety using a scanning electron microscope (SEM), measuring their major axis lengths, and averaging them. When calculating the average particle size of the primary particles, the number of primary particles to be evaluated is not particularly limited.
[0033] For example, when the positive electrode active material contains secondary particles, it is preferable to select 10 to 20 secondary particles, select primary particles from each of the selected secondary particles, and then select a total of 20 to 30 primary particles, and measure the major axis length of the selected primary particles.
[0034] In addition, when the positive electrode active material contains a single primary particle that does not constitute a secondary particle, it is preferable to evaluate 5 or more primary particles of the positive electrode active material. There is no particular upper limit on the number of primary particles to be evaluated, but it is preferable to evaluate, for example, 20 or less.
[0035] When the positive electrode active material contains only secondary particles, the above number of secondary particles can be selected from the secondary particles, and the above number of primary particles can be selected in total from each secondary particle. The lengths of the major axes of the selected primary particles can then be measured, and the average value can be used as the average particle size of the primary particles of the positive electrode active material.
[0036] When the positive electrode active material contains both secondary particles and single primary particles, the above-mentioned number of primary particles can be selected for each of the selected number of secondary particles and the single primary particles. Then, the lengths of the major axes of all the selected primary particles can be measured, and the average value can be regarded as the average particle size of the primary particles of the positive electrode active material.
[0037] By setting the average particle size of the primary particles of the positive electrode active material within the above range, when the positive electrode active material is applied to a secondary battery, it is possible to particularly improve both the battery capacity and the cycle characteristics, and to achieve a balance between them. [Method of manufacturing positive electrode active material for lithium ion secondary batteries] The method for producing the positive electrode active material for a lithium ion secondary battery is not particularly limited as long as the positive electrode active material having the above characteristics can be obtained. Hereinafter, an example of the method for producing the positive electrode active material according to the present embodiment will be described.
[0038] As described above, according to the method for producing a positive electrode active material of this embodiment, the positive electrode active material already described can be produced, and therefore some of the matters already described will not be described again.
[0039] The method for producing a positive electrode active material of the present embodiment is a method for producing a positive electrode active material for a lithium ion secondary battery including secondary particles in which a plurality of primary particles are aggregated together, and can be carried out, for example, according to flow 10 shown in Fig. 1. That is, the method for producing a positive electrode active material of the present embodiment can include a mixing step (S1), a milling step (S2), and a heat treatment step (S3).
[0040] In the mixing step (S1), a lithium transition metal composite oxide having a layered rock salt structure and lithium phosphate are mixed to prepare a mixture.
[0041] In the milling step (S2), mechanical stress is applied to the mixture obtained in the mixing step (S1), and a milled product having an amorphous or low-crystalline NiO-like rock salt structure can be obtained.
[0042] In the heat treatment step (S3), the milled product obtained in the milling step (S2) can be heated at a temperature of 620° C. or more and 700° C. or less by increasing the temperature at a rate of 2° C. / min or less.
[0043] An example of the configuration of each step will be described below. (1) Mixing process (S1) In the mixing step (S1), as described above, a lithium transition metal composite oxide and lithium phosphate can be mixed to prepare a mixture.
[0044] The lithium transition metal composite oxide subjected to the mixing step (S1) has a layered rock salt structure.
[0045] The composition of the lithium transition metal composite oxide is not particularly limited and can be selected according to the intended positive electrode active material. The lithium transition metal composite oxide is, for example, represented by the general formula: Li s´ Ni 1-x´-y´-z´ Co x´ Mn y´ M z´ O 2+β It is preferable that the formula is represented by the formula:
[0046] In the above general formula, x', y', z', s', and β preferably satisfy 0≦x'≦0.35, 0≦y'≦0.35, 0≦z'≦0.10, 1.00≦s'<1.30, and 0≦β≦0.2. Furthermore, the element M is preferably at least one element selected from V, Mg, Mo, Nb, Ti, W, and Al.
[0047] Lithium phosphate can be represented as Li3PO4.
[0048] In the mixing step (S1), the method for mixing the lithium transition metal composite oxide and the lithium phosphate is not particularly limited, and they can be mixed in a mortar, for example.
[0049] In the mixing step (S1), the ratio of the lithium transition metal composite oxide and the lithium phosphate to be mixed is not particularly limited, but it is preferable to mix them so that the content ratio of lithium phosphate in the resulting mixture is the target composition. Therefore, for example, in the mixing step, it is preferable to mix lithium phosphate in a ratio of more than 0 mol% and less than 10 mol% in terms of the substance amount ratio of the total of lithium phosphate and lithium transition metal composite oxide contained in the resulting mixture. (2) Milling process In the milling step (S2), mechanical stress is applied to the mixture obtained in the mixing step (S1). By applying mechanical stress to the mixture, the lithium transition metal composite oxide having a layered rock-salt structure and lithium phosphate can be converted into a milled product having an amorphous or low-crystalline NiO-like rock-salt structure.
[0050] Although the method of applying mechanical stress is not particularly limited, it is preferable to use mechanical milling. By using mechanical milling, it becomes easier to convert the lithium transition metal composite oxide having a layered rock-salt crystal structure and lithium phosphate into an amorphous or low-crystalline NiO-like rock-salt structure.
[0051] An amorphous or low-crystalline NiO-like rock-salt structure means that in the XRD pattern of the milled product after the milling process, the half-width of the diffraction peak of the (200) plane seen at 44° to 45° is 0.5° or more after background processing, etc. (3) Heat treatment process In the heat treatment step (S3), the milled product having an amorphous or low-crystalline NiO-like rock-salt structure obtained in the milling step (S2) can be heat-treated. By carrying out the heat treatment step, it is possible to obtain a lithium transition metal composite oxide having a layered rock-salt structure in which lithium phosphate is crystallized and dispersed. In addition, by carrying out the above-mentioned milling step in combination with the heat treatment step, the ratio of elements other than lithium in the Li site (3b site) can be easily set within a desired range.
[0052] In the heat treatment step (S3), only the lithium transition metal composite oxide has a layered rock-salt structure, and the lithium phosphate does not have a layered rock-salt structure.
[0053] By carrying out the heat treatment step (S3), the crystallized lithium phosphate can cover the surface of the primary particles of the lithium transition metal composite oxide having a layered rock-salt structure, and can be dispersed inside or on the surface of the secondary particles of the lithium transition metal composite oxide having a layered rock-salt structure. The lithium phosphate can be, for example, in the form of fine crystals. (Heat treatment temperature) In the heat treatment step (S3), the heat treatment is preferably performed at a temperature (heat treatment temperature) of 620° C. or more and 700° C. or less, and more preferably at a temperature of 620° C. or more and 680° C. or less. By performing the heat treatment within the above temperature range, the crystallized lithium phosphate can easily coat the surfaces of the primary particles of the lithium transition metal composite oxide having a layered rock-salt structure and be dispersed inside or on the surfaces of the secondary particles of the lithium transition metal composite oxide having a layered rock-salt structure.
[0054] In the heat treatment step (S3), the temperature is preferably increased to the heat treatment temperature at a rate (temperature increase rate) of 2° C. / min or less, more preferably 0.1° C. / min to 1° C. / min.
[0055] By setting the temperature rise rate at 2° C. / min or less, the reaction in the milled product can proceed uniformly, and the crystal growth of the lithium transition metal composite oxide can be promoted.
[0056] The holding time at the heat treatment temperature is not particularly limited, but is preferably 10 hours or more, and more preferably 10 hours or more and 48 hours or less.
[0057] In the heat treatment step, for example, the temperature can be raised to the heat treatment temperature, maintained for a predetermined time, and then cooled to room temperature. (atmosphere) The heat treatment atmosphere is preferably an oxidizing atmosphere. The oxidizing atmosphere preferably has an oxygen concentration of 80% by volume or more, more preferably an oxygen concentration of 85% by volume or more. The oxidizing atmosphere can also be an oxygen atmosphere, so the oxygen concentration can be 100% by volume or less.
[0058] The method for producing a positive electrode active material according to the present embodiment may further include any step as necessary. For example, the method may further include a lithium transition metal composite oxide production step of preparing a lithium transition metal composite oxide to be subjected to the above-mentioned mixing step. (4) Lithium transition metal composite oxide manufacturing process The lithium transition metal composite oxide production process may include, for example, a composite hydroxide production process, a heating process, and a calcination process, which will be described below. Note that the lithium transition metal composite oxide production process may include only one of the above processes. (4-1) Complex hydroxide production process The composite hydroxide production step is a step of obtaining a composite hydroxide as a coprecipitate in a reaction aqueous solution obtained by mixing a mixed aqueous solution containing a metal salt with an alkaline aqueous solution.
[0059] The mixed aqueous solution may contain, as the metal salt, a metal salt of a metal other than the lithium contained in the lithium transition metal composite oxide. The mixed aqueous solution may contain, as the metal salt, a nickel salt such as nickel sulfate (II), a cobalt salt such as cobalt sulfate (II), a manganese salt such as manganese sulfate (II), or a metal salt of element M. The element M used in the metal salt of element M may be at least one element selected from the group consisting of V, Mg, Mo, Nb, Ti, W, and Al.
[0060] The mixed aqueous solution can contain the metal salts in a ratio that matches the target composition of the lithium transition metal composite oxide.
[0061] The mixed aqueous solution containing the metal salt is supplied together with an aqueous alkali solution into a reaction tank to form a reaction aqueous solution, and a composite hydroxide can be obtained as a coprecipitate. When the composite hydroxide contains multiple types of metals, it is necessary to supply multiple types of metal salts as a mixed aqueous solution containing the metal salts into the reaction aqueous solution, but for example, a mixed aqueous solution may be prepared and supplied for each metal salt. Alternatively, one or more mixed aqueous solutions containing multiple types of metal salts may be prepared and supplied.
[0062] The alkaline aqueous solution is not particularly limited, but for example, an aqueous solution of an alkali metal hydroxide such as sodium hydroxide or potassium hydroxide can be used.
[0063] If necessary, a complexing agent can be added to the reaction aqueous solution, such as one or more of aqueous solutions of ammonia, ammonium sulfate, and ammonium chloride.
[0064] The mixed aqueous solution and an alkaline aqueous solution are mixed to prepare a reaction aqueous solution, and the pH value of the reaction aqueous solution is controlled to obtain a composite hydroxide. In this case, the pH value of the reaction aqueous solution is not particularly limited, but it is preferable to control it so that it is alkaline, for example.
[0065] When no complexing agent is added to the reaction aqueous solution, the pH value of the reaction aqueous solution is preferably controlled to be 9 or more and 11 or less. In addition, in this case, the temperature of the reaction aqueous solution is preferably set to be in the range of 40°C or more and 80°C or less. By setting the pH value and temperature of the reaction aqueous solution in the above ranges, the reaction rate can be set in an appropriate range. In addition, the solubility of ions of metals such as nickel becomes favorable, and the formation of fine particles due to crystallization can be prevented.
[0066] Specifically, by setting the pH value of the reaction solution to 11 or less, the formation of fine particles can be suppressed and spherical particles can be easily formed. This improves the filterability when the obtained composite hydroxide is filtered. By setting the pH value of the reaction solution to 9 or more, the production rate of the composite hydroxide can be set to a suitable rate, and a composite hydroxide of the target composition can be easily produced.
[0067] In addition, by setting the temperature of the reaction aqueous solution at 40° C. or higher, the reaction rate can be made appropriate. By setting the temperature of the reaction aqueous solution at 80° C. or lower, the amount of water evaporation can be suppressed, and the slurry concentration can be prevented from increasing. As a result, a composite hydroxide of the target composition can be easily obtained.
[0068] As mentioned above, a complexing agent can be added to the aqueous reaction solution, which can increase the solubility of metals such as nickel.
[0069] When a complexing agent is used, the pH value of the reaction solution is preferably controlled to be 10 or more and 12.5 or less. In this case, the temperature of the reaction solution is preferably set in the range of 40°C or more and 60°C or less.
[0070] The concentration of the complexing agent in the reaction aqueous solution is not particularly limited, but is preferably kept constant within the range of 3 g / L to 25 g / L. By making the concentration of the complexing agent 3 g / L or more, the fluctuation of the solubility of the metal ions in the reaction aqueous solution can be suppressed. Therefore, a composite hydroxide with a uniform shape and particle size can be formed, and the width of the particle size distribution can also be suppressed.
[0071] Furthermore, by setting the concentration of the complexing agent in the reaction aqueous solution to 25 g / L or less, the solubility of the metal ions can be adjusted to a particularly suitable range, and a composite hydroxide of the desired composition can be easily obtained.
[0072] When the complexing agent concentration in the reaction aqueous solution fluctuates, the solubility of metal ions fluctuates, so it is preferable to keep the complexing agent concentration at a constant value, and for example, it is preferable to keep the complexing agent concentration at a desired concentration with the upper and lower limits of about 5 g / L or less. As mentioned above, ammonia water or the like can be used as the complexing agent, so the above complexing agent concentration can also be called an ammonia concentration. (4-2) Heating process The heating step is a step of heating the composite hydroxide produced in the composite hydroxide production step, and can be carried out as necessary. The heating step can remove moisture contained in the composite hydroxide. By carrying out this heating step, the moisture remaining until the calcination step can be reduced. In addition, depending on the conditions of the heating step, the composite hydroxide can be converted into a composite oxide. By carrying out the heating step, it is possible to prevent variations in the lithium transition metal composite oxide produced, the number of metal atoms in the positive electrode active material, and the ratio of the number of lithium atoms.
[0073] In the heating step, it is not necessary to convert all the composite hydroxides to composite oxides, since it is sufficient to remove moisture to such an extent that there is no variation in the number of metal atoms or the ratio of the number of lithium atoms in the lithium transition metal composite oxide or the like. When the heating step is performed, the composite hydroxide is heated to a temperature at which the residual moisture is removed, and the heating temperature is not particularly limited, but is preferably 105°C or higher and 800°C or lower. If the composite hydroxide is heated to 105°C or higher, the residual moisture can be removed in a short time. In addition, since it tends to take a long time to remove the residual moisture at temperatures lower than 105°C, it is preferable to heat the composite hydroxide at 105°C or higher as described above. In addition, by setting the heating temperature to 800°C or lower, it is possible to prevent the particles converted to the composite oxide from sintering and agglomerating.
[0074] The atmosphere in which the heat treatment is carried out is not particularly limited, but it is preferable to carry out the heat treatment in an air stream, which is easy to carry out. (4-3) Firing process In the calcination step, a lithium mixture obtained by mixing the heat-treated product obtained in the heating step with one or more selected from lithium and lithium compounds can be calcined. Note that instead of the heat-treated product, the composite hydroxide prepared in the composite hydroxide production step can be used as is. By the calcination step, a lithium transition metal composite oxide having a layered rock salt structure can be obtained.
[0075] The lithium mixture is preferably such that the ratio (Li / Me) of the number of atoms of metal elements other than lithium (Me) in the lithium mixture to the number of atoms of lithium element (Li) is 1.00 or more and less than 1.30. In other words, it is preferable to mix so that the Li / Me in the lithium mixture is the same as the Li / Me in the lithium transition metal composite oxide that is the product. This is because the Li / Me in the lithium mixture is equal to the Li / Me in the lithium transition metal composite oxide since the Li / Me does not change before and after the firing process. The above Me means the total number of atoms of metal elements other than lithium in the lithium mixture or the lithium transition metal composite oxide, and examples thereof include the total number of atoms of nickel, cobalt, manganese, and element M.
[0076] The lithium compound used in preparing the lithium mixture is not particularly limited, but for example, one or more selected from the lithium compound group consisting of lithium hydroxide, lithium nitrate, and lithium carbonate can be preferably used from the viewpoint of easy availability. As the lithium compound used in preparing the lithium mixture, a mixture of two or more selected from the above lithium compound group can also be used.
[0077] As the lithium compound, it is more preferable to use lithium hydroxide, particularly in consideration of ease of handling and stability of quality.
[0078] It is preferable to thoroughly mix the lithium mixture before firing in the firing step. By thoroughly mixing before firing, the Li / Me variation between individual particles is eliminated, and particularly high battery characteristics can be obtained.
[0079] In the calcination step, the lithium mixture is calcined to obtain a lithium transition metal composite oxide. When the lithium mixture is calcined in the calcination step, lithium in the lithium-containing substance is diffused into the composite hydroxide obtained in the composite hydroxide production step or the heating step, and a lithium transition metal composite oxide having a layered rock salt structure is formed.
[0080] The lithium mixture is preferably fired at 600°C or higher and 850°C or lower, more preferably 650°C or higher and 820°C or lower. By setting the firing temperature at 600°C or higher, lithium can be sufficiently diffused into the composite hydroxide, etc., and the crystallinity of the resulting lithium transition metal composite oxide can be increased. Furthermore, by setting the firing temperature at 850°C or lower, sintering between particles of the resulting lithium transition metal composite oxide can be suppressed, and abnormal grain growth can be suppressed. Therefore, the particles of the lithium transition metal composite oxide obtained after firing can be prevented from becoming coarse.
[0081] The baking time is not particularly limited, but is preferably at least 3 hours, and more preferably 6 hours to 24 hours.
[0082] The atmosphere during the calcination is preferably an oxidizing atmosphere, and more preferably an atmosphere with an oxygen concentration of 18% by volume or more and 100% by volume or less. The calcination step is preferably carried out in air or an oxygen stream. By setting the oxygen concentration in the calcination atmosphere to 18% by volume or more, for example, even if a composite hydroxide or the like is contained in the particles, it can be sufficiently oxidized, and the crystallinity of the lithium transition metal composite oxide can be improved. In particular, in consideration of the battery characteristics, it is preferable to carry out the calcination in an oxygen stream. [Lithium-ion secondary battery] The lithium ion secondary battery of this embodiment includes at least a positive electrode, a negative electrode, and a non-aqueous electrolyte, and the positive electrode can include the above-described positive electrode active material for lithium ion secondary batteries.
[0083] Hereinafter, one configuration example of the secondary battery of this embodiment will be described for each component. The secondary battery of this embodiment includes, for example, a positive electrode, a negative electrode, and a non-aqueous electrolyte, and is composed of the same components as a general lithium-ion secondary battery. Note that the embodiment described below is merely an example, and the lithium-ion secondary battery of this embodiment can be embodied in various forms that have been modified and improved based on the knowledge of those skilled in the art, including the following embodiment. In addition, the secondary battery is not particularly limited in its use. (positive electrode) The positive electrode of the secondary battery of this embodiment can contain the above-mentioned positive electrode active material.
[0084] An example of a method for manufacturing a positive electrode is described below. First, the positive electrode active material (powder), conductive agent, and binder are mixed to prepare a positive electrode mixture, and activated carbon and a solvent for viscosity adjustment, etc. are added as necessary, and the mixture is kneaded to prepare a positive electrode mixture paste.
[0085] The mixing ratio of each material in the positive electrode mixture is a factor that determines the performance of the lithium ion secondary battery, and can be adjusted depending on the application. The mixing ratio of the materials can be the same as that of the positive electrode of a known lithium ion secondary battery, and for example, when the total mass of the solid content of the positive electrode mixture excluding the solvent is taken as 100 mass%, the positive electrode active material can be contained in a ratio of 60 mass% to 95 mass%, the conductive agent can be contained in a ratio of 1 mass% to 20 mass%, and the binder can be contained in a ratio of 1 mass% to 20 mass%.
[0086] The obtained positive electrode mixture paste is applied to the surface of a current collector made of, for example, aluminum foil, and dried to remove the solvent, thereby producing a sheet-like positive electrode. If necessary, pressure can be applied by a roll press or the like to increase the electrode density. The sheet-like positive electrode thus obtained can be cut to an appropriate size according to the desired battery and used for the production of the battery.
[0087] As the conductive agent, for example, graphite (natural graphite, artificial graphite, expanded graphite, etc.) and carbon black-based materials such as acetylene black and Ketjen Black (registered trademark) can be used.
[0088] The binder serves to bind the positive electrode active material particles together, and may be, for example, one or more selected from polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), fluororubber, ethylene propylene diene rubber, styrene butadiene, cellulose-based resin, polyacrylic acid, and the like.
[0089] If necessary, a solvent for dispersing the positive electrode active material, conductive agent, etc. and dissolving the binder can be added to the positive electrode mixture. Specifically, an organic solvent such as N-methyl-2-pyrrolidone can be used as the solvent. Activated carbon can also be added to the positive electrode mixture to increase the electric double layer capacity.
[0090] The method for producing the positive electrode is not limited to the above-mentioned example, and other methods may be used. For example, the positive electrode may be produced by pressing the positive electrode mixture and then drying it in a vacuum atmosphere. (Negative electrode) For the negative electrode, metallic lithium, a lithium alloy, etc. may be used. The negative electrode may be prepared by mixing a binder with a negative electrode active material capable of absorbing and desorbing lithium ions, adding an appropriate solvent to make a paste-like negative electrode mixture, applying the mixture to the surface of a metal foil current collector such as copper, drying it, and compressing it to increase the electrode density as necessary.
[0091] As the negative electrode active material, for example, natural graphite, artificial graphite, sintered organic compounds such as phenol resin, and powder of carbon material such as coke can be used. In this case, as with the positive electrode, fluorine-containing resin such as PVDF can be used as the negative electrode binder, and an organic solvent such as N-methyl-2-pyrrolidone can be used as the solvent for dispersing these active materials and binders. (Separator) A separator may be sandwiched between the positive electrode and the negative electrode as necessary. The separator separates the positive electrode and the negative electrode and holds the electrolyte, and any known separator may be used, such as a thin membrane made of polyethylene or polypropylene having many minute pores. (Non-aqueous electrolyte) As the non-aqueous electrolyte, for example, a non-aqueous electrolytic solution can be used.
[0092] As the non-aqueous electrolyte, for example, a solution in which a lithium salt as a supporting salt is dissolved in an organic solvent can be used. Alternatively, as the non-aqueous electrolyte, a solution in which a lithium salt is dissolved in an ionic liquid can be used. Note that the ionic liquid refers to a salt that is composed of cations and anions other than lithium ions and is liquid even at room temperature.
[0093] The organic solvent may be one selected from cyclic carbonates such as ethylene carbonate, propylene carbonate, butylene carbonate, and trifluoropropylene carbonate; chain carbonates such as diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, and dipropyl carbonate; ether compounds such as tetrahydrofuran, 2-methyltetrahydrofuran, and dimethoxyethane; sulfur compounds such as ethyl methyl sulfone and butane sultone; and phosphorus compounds such as triethyl phosphate and trioctyl phosphate. Two or more of these organic solvents may be used in combination.
[0094] The supporting salt may be LiPF6, LiBF4, LiClO4, LiAsF6, LiN(CF3SO2)2, or a composite salt thereof. Furthermore, the non-aqueous electrolyte may contain a radical scavenger, a surfactant, a flame retardant, and the like.
[0095] The non-aqueous electrolyte may be a solid electrolyte. The solid electrolyte has a property of being able to withstand high voltage. Examples of the solid electrolyte include inorganic solid electrolytes and organic solid electrolytes.
[0096] Examples of the inorganic solid electrolyte include oxide-based solid electrolytes and sulfide-based solid electrolytes.
[0097] The oxide-based solid electrolyte is not particularly limited, and for example, an oxide-based solid electrolyte containing oxygen (O) and having lithium ion conductivity and electronic insulation can be suitably used. Examples of the oxide-based solid electrolyte include lithium phosphate (Li3PO4), Li3PO4N X , LiBON X , LiNbO3, LiTaO3, Li2SiO3, Li4SiO4-Li3PO4, Li4SiO4-Li3VO4, Li2O-B2O3-P2O5, Li2O-SiO2, Li2O-B2O3-ZnO, Li 1+X Al X Ti 2-X (PO4)3(0≦X≦1), Li 1+X Al X Ge 2-X (PO4)3(0≦X≦1), LiTi2(PO4)3, Li 3X La 2 / 3-X TiO3(0≦X≦2 / 3), Li5La3Ta2O 12 , Li7La3Zr2O 12 , Li6BaLa2Ta2O 12 , Li 3.6 S 0.6 P 0.4 One or more types selected from O4, etc. can be used.
[0098] The sulfide-based solid electrolyte is not particularly limited, and for example, one containing sulfur (S) and having lithium ion conductivity and electronic insulation can be suitably used. For example, the sulfide-based solid electrolyte can be one or more selected from Li2S-P2S5, Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-Li2S-B2S3, Li3PO4-Li2S-Si2S, Li3PO4-Li2S-SiS2, LiPO4-Li2S-SiS, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, etc.
[0099] As the inorganic solid electrolyte, materials other than those mentioned above may be used, for example, Li3N, LiI, Li3N-LiI-LiOH, etc. may be used.
[0100] The organic solid electrolyte is not particularly limited as long as it is a polymer compound exhibiting ion conductivity, and examples of the organic solid electrolyte that can be used include polyethylene oxide, polypropylene oxide, copolymers thereof, etc. The organic solid electrolyte may also contain a supporting salt (lithium salt). (Shape and structure of lithium-ion secondary batteries) The lithium ion secondary battery of the present embodiment described above can be made into various shapes such as a cylindrical type, a laminated type, etc. Regardless of the shape, if the secondary battery of the present embodiment uses a non-aqueous electrolyte as the non-aqueous electrolyte, the positive electrode and the negative electrode are laminated via a separator to form an electrode body, the obtained electrode body is impregnated with a non-aqueous electrolyte, and the positive electrode current collector and the positive electrode terminal connected to the outside, and the negative electrode current collector and the negative electrode terminal connected to the outside are connected using a current collecting lead or the like, and the battery case is sealed to form a structure.
[0101] As described above, the secondary battery of the present embodiment is not limited to a form using a non-aqueous electrolyte solution as a non-aqueous electrolyte, and may be, for example, a secondary battery using a solid non-aqueous electrolyte, i.e., an all-solid-state battery. When making an all-solid-state battery, the configuration other than the positive electrode active material may be changed as necessary.
[0102] The secondary battery of this embodiment can be used for various purposes. Since the secondary battery of this embodiment can be a high-capacity, high-output secondary battery, it is suitable for use as a power source for small portable electronic devices (such as notebook personal computers and mobile phone terminals) that always require high capacity, and is also suitable as a power source for electric vehicles that require high output.
[0103] In addition, the secondary battery of this embodiment can be made compact and have high output, making it suitable as a power source for electric vehicles that are limited in installation space. The secondary battery of this embodiment can be used not only as a power source for electric vehicles that are driven purely by electrical energy, but also as a power source for so-called hybrid vehicles that are used in conjunction with combustion engines such as gasoline engines and diesel engines. EXAMPLES
[0104] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples in any way.
[0105] First, the evaluation methods of the positive electrode active materials and secondary batteries obtained in the following Examples and Comparative Examples will be described. (Evaluation of Positive Electrode Active Material) The obtained positive electrode active material was evaluated as follows.
[0106] (a) Evaluation of composition The composition of the positive electrode active material was analyzed by ICP emission spectrometry. The evaluation results are shown in the "Composition" column of Table 1. The ratio of lithium phosphate shown in the composition column means the mass ratio to the lithium transition metal composite oxide.
[0107] (b) The proportion of elements other than lithium in the lithium sites (3b sites) and the proportion of lithium in the metal sites (3a sites) About 2 g of the positive electrode active material prepared in the following Examples and Comparative Examples was filled into a vanadium tube, which was then completely sealed. Neutron diffraction measurements were then performed at BL20 (iMATERIA, Ibaraki Prefecture) at the Japan Proton Accelerator Research Complex (J-PARC) under conditions that yielded an intensity of 10,000 cps or more in double frame mode.
[0108] The neutron diffraction pattern obtained from the rear detector bank was subjected to Rietveld analysis using the analysis software Z-Code. At this time, the space group was set to R-3m, and lithium and a mixed metal element (a metal element other than lithium on the lithium site) were set as chemical species at the 3b site, and a metal element other than lithium and mixed lithium were set as chemical species at the 3a site. The metal elements other than lithium refer to nickel, cobalt, and element M, and were selected and set according to the composition of each example. The metal element other than lithium was nickel in Examples 1 to 4 and Comparative Example 1. The metal elements other than lithium were nickel, cobalt, and aluminum in Example 5, and nickel, manganese, and cobalt in Example 6.
[0109] After refining the scale factor, lattice constant, and global parameters, the site occupancy and atomic coordinates were refined. The atomic displacement parameters for lithium were 0.9 to 1.0 Å. 2 , nickel, cobalt, and element M: 0.3-0.5 Å 2 , Oxygen: 0.6~0.8Å 2 The site occupancy rate was fixed within the range. After refining the site occupancy rate and atomic coordinates, the reliability parameter S value was deemed to have converged at 3.0 or less. The site occupancy rate of metal elements other than lithium at the obtained lithium site (3b site) was calculated, and the results are shown in the column of Table 1 titled "Proportion of elements other than Li at the Li site (3b site)." In addition, the site occupancy rate of lithium elements at the obtained metal site (3b site) was calculated, and the results are shown in the column of Table 1 titled "Proportion of Li element at the metal site (3a site)."
[0110] Powder neutron diffraction measurements can also be performed using a High Resolution Powder Diffractometer (HRPD) installed in the Japan Atomic Energy Agency's JRR-3 reactor or the Super HRPD at J-PARC.
[0111] (c) Average particle size of primary particles In the SEM observation image of the lithium transition metal composite oxide particles, 15 secondary particles that could be observed in their entirety by image analysis were selected, and primary particles were selected from each selected secondary particle. At this time, a total of 30 primary particles were selected. The major axis lengths of the selected primary particles were then measured, and the average value was taken as the average primary particle diameter.
[0112] The evaluation results are shown in Table 1 in the column "Average particle size of primary particles." (Production and evaluation of lithium-ion secondary batteries) (a) Preparation of coin-type battery Coin type batteries were produced using the positive electrode active materials produced in the following Examples and Comparative Examples.
[0113] Specifically, 0.170 g of the positive electrode active material obtained in the following Examples and Comparative Examples was weighed out in a glove box under an argon atmosphere. The weighed positive electrode active material was then placed in a container together with 0.010 g of acetylene black, 0.250 g of polyvinylidene fluoride (PVDF) solution (8% solution manufactured by Kureha) and 70 μL of N-methyl-2-pyrrolidone (NMP), and mixed with a stirrer (AR-100 manufactured by Thinky).
[0114] The slurry obtained by stirring was applied to an aluminum foil and vacuum dried at room temperature for 2 hours, and then vacuum dried at 120°C for 2 hours to obtain an electrode.
[0115] The obtained electrode was punched out to a diameter of 10 mm, the weight was measured, and this was used as a positive electrode.
[0116] Metallic lithium was used as the negative electrode, and a polyethylene (PE) porous film was used as the separator, and the positive electrode, separator, and negative electrode were laminated in that order. The laminate of the positive electrode, separator, and negative electrode was impregnated with an electrolyte and sealed between the positive electrode can and the negative electrode can. A gasket was placed between the positive electrode can and the negative electrode can, and the two components were fixed in place to restrict relative movement so as to maintain a non-contact state, i.e., an electrically insulated state.
[0117] The electrolyte used was a 3:7 mixture (volume ratio) of ethylene carbonate (EC) and diethyl carbonate (DEC) with 1M LiPF6 as the supporting electrolyte.
[0118] The coin-type battery was fabricated in a dry room with a dew point controlled at -60°C.
[0119] (b) Evaluation of discharge capacity and cycle characteristics The capacity retention rate, which indicates cycle characteristics, was evaluated by measuring the capacity retention rate after 100 charge / discharge cycles for a coin-type battery.
[0120] Specifically, a current of 30 mA / g was applied to the coin battery, and the battery was charged to a cutoff voltage of 4.5 V and then discharged to a cutoff voltage of 2.5 V. This cycle was repeated 100 times. The capacity retention rate, which is the ratio of the discharge capacity at the 100th cycle after conditioning to the discharge capacity at the 1st cycle, was calculated and evaluated.
[0121] The discharge capacity at the first cycle is shown in the "Discharge Capacity" column of Table 1, and the capacity retention rate is shown in the "Cycle Characteristics" column of Table 1. (Production conditions of positive electrode active material) [Example 1] (1) Lithium transition metal composite oxide manufacturing process Nickel hydroxide obtained by a known method and lithium hydroxide monohydrate were mixed to prepare a lithium mixture.
[0122] In the mixing process, nickel hydroxide and lithium hydroxide monohydrate were thoroughly mixed using a shaker mixer (Willi & Bachofen (WAB), model: TURBULA Type T2C) to prepare a raw material mixture.
[0123] In the mixing step, the raw materials were weighed and mixed so that the atomic ratio (Li / Ni) of the number of lithium atoms (Li) to the number of nickel atoms (Ni) in the resulting lithium mixture would be 1.00.
[0124] This lithium mixture was calcined under an oxygen atmosphere (calcination step).
[0125] In the firing step, the temperature was raised to 650° C., and the firing temperature was maintained at 650° C. for 12 hours. After maintaining the firing temperature, the material was cooled to room temperature.
[0126] The XRD pattern of the lithium transition metal composite oxide obtained after firing was measured using a powder X-ray diffractometer (manufactured by Bruker, product name: D2 PHASER), and it was confirmed that the lithium transition metal composite oxide had a layered rock salt structure. (2)Mixing process In the mixing step, 0.97 g of the lithium transition metal composite oxide having the layered rock salt structure and 0.03 g of lithium phosphate were weighed out on an electronic balance in a glove box under an argon atmosphere, and thoroughly mixed in an agate mortar to prepare a mixture. (3) Milling process In the milling step, the mixture obtained in the mixing step was placed in a 40 mL volumetric container made of zirconia together with 59 g of φ5 mm zirconia balls in the glove box.
[0127] Then, mechanical milling was performed a total of 96 times using a Fritsch planetary ball mill (P-7), which consisted of processing at 600 rpm for 15 min and then stopping for 3 min.
[0128] Thereafter, in a glove box under an argon atmosphere, the zirconia container was opened, the zirconia balls were removed, and the milled product obtained by the mechanical milling process was taken out.
[0129] The XRD pattern of the milled product was measured using a powder X-ray diffractometer (D2 PHASER manufactured by Bruker) with CuKα radiation, tube voltage of 30 V, and tube current of 10 mA, in the region of 2θ between 10° and 100°. As a result, the half-width of the diffraction peak of the (200) plane seen at 44° to 45° was 0.5° or more, and a broad diffraction peak derived from the NiO-like rock salt structure was observed. Therefore, it was confirmed that the product has an amorphous or low-crystalline NiO-like rock salt structure. (4) Heat treatment process The milled product obtained in the milling step was heated in a firing furnace in an oxygen atmosphere to a heat treatment temperature of 650° C. at a heating rate of 1° C. / min, and then held at the heat treatment temperature for 12 hours to obtain a positive electrode active material.
[0130] The obtained positive electrode active material was embedded in a thermosetting resin and then polished with a cross-section polisher (SM-09010, manufactured by JEOL Ltd.). The cross sections of the obtained particles were observed for 100 particles using a Schottky field emission scanning electron microscope (Ultra 55, manufactured by Carl Zeiss). As a result, it was confirmed that the positive electrode active material was composed of secondary particles in which multiple primary particles were aggregated together.
[0131] In the following Examples 2 to 6, the positive electrode active materials were evaluated in the same manner, and it was confirmed that the obtained positive electrode active materials were composed of secondary particles in which a plurality of primary particles were aggregated together.
[0132] To confirm the crystal structure of the obtained positive electrode active material, the XRD pattern was measured using a powder X-ray diffractometer. As a result, it was confirmed that the lithium transition metal composite oxide has a layered rock salt structure. In addition, since the diffraction peak of lithium phosphate was faintly confirmed, it was confirmed that the crystallized lithium phosphate was dispersed on the submicron order.
[0133] In the following Examples 2 to 6, the positive electrode active material was evaluated in the same manner, and it was confirmed that the lithium transition metal composite oxide had a layered rock salt structure. Also, in the following Examples 2 to 6, the diffraction peak of lithium phosphate was faintly confirmed, and it was confirmed that the crystallized lithium phosphate was dispersed on the submicron order.
[0134] The obtained positive electrode active material was observed using SEM-EDS (manufactured by JEOL Ltd., product name: JCM-6000) to obtain an element mapping image. As a result, it was confirmed that phosphorus was dispersed on the submicron order, and from the phosphorus distribution, lithium phosphate covered at least a part of the surface of the primary particles of the lithium transition metal composite oxide, and was dispersed inside or on the surface of the secondary particles of the lithium transition metal composite oxide.
[0135] The positive electrode active material was observed by SEM-EDS in the same manner in the following Examples 2 to 6. As a result, it was confirmed that phosphorus was dispersed on the submicron order, and from the phosphorus distribution, lithium phosphate covered at least a part of the surface of the primary particles of the lithium transition metal composite oxide, and was dispersed inside or on the surface of the secondary particles of the lithium transition metal composite oxide.
[0136] Other evaluation results are shown in Table 1.
[0137] The composition of the obtained positive electrode active material was LiNiO2-3% Li3PO4 in terms of mass ratio as shown in Table 1, and 0.975LiNiO2-0.025Li3PO4 in terms of the ratio of the amounts of substances.
[0138] The positive electrode active material thus obtained was used to fabricate the coin-type battery described above, which was then evaluated. The evaluation results are shown in Table 1. [Examples 2 and 3] A positive electrode active material and a coin-type battery were produced and evaluated under the same conditions as in Example 1, except that the heat treatment temperature in the heat treatment step was changed.
[0139] The heat treatment temperature was 665°C in Example 2 and 635°C in Example 3.
[0140] The evaluation results are shown in Table 1. [Example 4] In the mixing step, 0.92 g of the lithium transition metal composite oxide prepared in Example 1 and 0.08 g of lithium phosphate were weighed out on an electronic balance and thoroughly mixed in an agate mortar to prepare a mixture, which was then subjected to the milling step and the heat treatment step. A positive electrode active material and a coin-type battery were produced and evaluated under the same conditions as in Example 1, except for the above points.
[0141] The composition of the obtained positive electrode active material was LiNiO2-9% Li3PO4 in terms of mass ratio as shown in Table 1, and 0.929LiNiO2-0.071Li3PO4 in terms of the ratio of the amounts of substances.
[0142] The evaluation results are shown in Table 1. [Example 5] The lithium transition metal composite oxide manufacturing process was not carried out, and LiNi 0.85 Co 0.10 Al 0.05 O2 was subjected to the mixing process. Then, 0.97 g of the lithium transition metal composite oxide and 0.03 g of lithium phosphate were weighed out using an electronic balance, thoroughly mixed in an agate mortar to prepare a mixture, and subjected to the milling process and heat treatment process. A positive electrode active material and a coin-type battery were produced and evaluated under the same conditions as in Example 1 except for the above points.
[0143] The composition of the obtained positive electrode active material was LiNi 0.85 Co 0.10 Al 0.05O2-3%Li3PO4, and the ratio of the amount of substance is 0.976LiNi 0.85 Co 0.10 Al 0.05 The formula is O2-0.024Li3PO4. [Example 6] The lithium transition metal composite oxide manufacturing process was not carried out, and LiNi 0.8 Mn 0.1 Co 0.1 O2 was subjected to the mixing process. Then, 0.97 g of the lithium transition metal composite oxide and 0.03 g of lithium phosphate were weighed out using an electronic balance, thoroughly mixed in an agate mortar to prepare a mixture, and subjected to the milling process and heat treatment process. A positive electrode active material and a coin-type battery were produced and evaluated under the same conditions as in Example 1 except for the above points.
[0144] The composition of the obtained positive electrode active material was LiNi 0.8 Mn 0.1 Co 0.1 O2-3%Li3PO4, and the ratio of the amount of substance is 0.975LiNi 0.8 Mn 0.1 Co 0.1 The formula is O2-0.025Li3PO4. [Comparative Example 1] In Comparative Example 1, lithium phosphate was not mixed in the mixing step, and the milling step was not performed. That is, the lithium transition metal composite oxide obtained in the lithium transition metal composite oxide production step was directly subjected to the heat treatment step. A positive electrode active material and a coin-type battery were produced and evaluated under the same conditions as in Example 1 except for the above points. The evaluation results are shown in Table 1. [Comparative Example 2] A positive electrode active material and a coin-type battery were produced and evaluated under the same conditions as in Example 1, except that the heat treatment temperature in the heat treatment step was changed to 610°C.
[0145] The evaluation results are shown in Table 1.
[0146] [Table 1] (Evaluation Results) As shown in Table 1, in Examples 1 to 6, positive electrode active materials were obtained that contained secondary particles in which a plurality of primary particles were aggregated together, a lithium transition metal composite oxide having a layered rock salt structure, and crystallized lithium phosphate, and in which the proportion of elements other than lithium in the lithium sites (3b sites) of the lithium transition metal composite oxide was 3% or more and 8% or less.
[0147] It was also confirmed that the positive electrode active materials obtained in Examples 1 to 6 have a higher capacity retention rate when applied to a lithium ion secondary battery, compared to the positive electrode active materials obtained in Comparative Examples 1 and 2 which do not satisfy the above requirements. That is, it was confirmed that positive electrode active materials excellent in cycle characteristics were obtained in Examples 1 to 6.
[0148] Moreover, it was confirmed that the positive electrode active materials obtained in Examples 1 to 6 had higher discharge capacities when applied to lithium ion secondary batteries, compared to the positive electrode active material obtained in Comparative Example 2. [Explanation of symbols]
[0149] S1 Mixing process S2 Milling process S3 Heat treatment process
Claims
1. A positive electrode active material for a lithium ion secondary battery, comprising secondary particles in which a plurality of primary particles are aggregated together, The present invention includes a lithium transition metal composite oxide having a layered rock salt structure and a crystallized lithium phosphate, In the crystal structure analysis by neutron diffraction of the lithium transition metal composite oxide having the layered rock salt structure, A positive electrode active material for a lithium ion secondary battery, in which the ratio of elements other than lithium in lithium sites (3b sites) is 3% or more and 8% or less.
2. 2. The positive electrode active material for a lithium ion secondary battery according to claim 1, wherein the average particle size of the primary particles is 20 nm or more and 250 nm or less.
3. 3. The positive electrode active material for a lithium ion secondary battery according to claim 1, wherein in a crystal structure analysis by neutron diffraction of the lithium transition metal composite oxide having the layered rock salt structure, a ratio of lithium elements occupying metal sites (3a sites) is 3% or more and 8% or less.
4. The positive electrode active material for a lithium ion secondary battery is represented by the general formula: kLi 3 P.O. 4 -(1-k)Li s Ni 1-x-y-z Co x Mn y M z O 2+α 3. The positive electrode active material for a lithium ion secondary battery according to claim 1, wherein k is at least one element selected from the group consisting of V, Mg, Mo, Nb, Ti, W, and Al, and 0≦x≦0.35, 0≦y≦0.35, 0≦z≦0.10, 1.00≦s<1.30, and 0≦α≦0.
2.
5. 3. The positive electrode active material for a lithium ion secondary battery according to claim 1, wherein the crystallized lithium phosphate covers at least a part of a surface of a primary particle of the lithium transition metal composite oxide having the layered rock salt structure, and is dispersed inside or on a surface of a secondary particle of the lithium transition metal composite oxide having the layered rock salt structure.
6. A method for producing a positive electrode active material for a lithium ion secondary battery, the method comprising the steps of: A mixing step of mixing a lithium transition metal composite oxide having a layered rock salt structure with lithium phosphate to prepare a mixture; a milling step of applying mechanical stress to the mixture obtained in the mixing step to obtain a milled product having an amorphous or low-crystalline NiO-like rock salt structure; and a heat treatment step of heating the milled product obtained in the milling step at a temperature of 620° C. or higher and 700° C. or lower at a rate of 2° C. / min or lower.
7. The battery includes at least a positive electrode, a negative electrode, and a non-aqueous electrolyte; A lithium ion secondary battery, wherein the positive electrode comprises the positive electrode active material for lithium ion secondary batteries according to claim 1 or 2.
Citation Information
Patent Citations
Lithium ion secondary battery, and method for manufacturing positive electrode active material for lithium ion secondary battery
JP2016110714A
Positive electrode mixture for nonaqueous electrolyte secondary battery, positive electrode, nonaqueous electrolyte secondary battery arranged by use thereof, and method for manufacturing positive electrode for nonaqueous electrolyte secondary battery
JP2020136093A